'The COVID-19 crisis is not the core problem': experiences, challenges, and concerns of Irish academia during the pandemic. Issue 2 (3rd April 2021) - Shankar, Kalpana; Phelan, Dean; Suri, Venkata Ratnadeep; Watermeyer, Richard; Knight, Cathryn; Crick, Tom
Abstract : This article, drawing on data from an international survey – distributed in the summer of 2020 – explores the experiences and concerns of academic staff ( n  = 167) working in universities in Ireland and their perceptions of their institutions' early response to the pandemic. Concerns related to transitioning to remote online working, impact on research productivity and culture, and work intensification, as intersected by enhanced managerialism, are ubiquitous to their accounts. As some respondents wrote of potential positive changes, particularly in the delivery of teaching, we conclude by suggesting potential avenues for building on successes in coping with the pandemic with some recommendations for mitigating some of the harms.